On documentaries, books and pedagogies. About Film and Reform. John Grierson and the documentary film movement - COLLELLDEMONT PUJADAS, EULÀLIA (Historia y Memoria de la Educación, 2022)
Review of the book Ian Aitken. Film and Reform. John Grierson and the documentary film movement. London-New York: Routledge, 2014 [1990],